(untitled) (Boulder, Colo., 2006)
Offers an overview of the state of affairs - and an examination of the potential for peaceful resolution. Representing all sides in the conflict over Kashmir, this book provides a forum for discussion of proposals for ending the conflict and of the possible paths toward settlement.
Keywords: National security,An ninh quốc gia; South Asia,Nam Á